Professional ethics & corporate social responsibility - Akinwumi, Akinniyi Joseph (Ado-Ekiti, Nigeria : Ona Ope Mi Po, 2013)
Emphasizes effective compliance with professional ethics and corporate social responsibility as the necessary conditions for personal, organisational and societal development. It also highlights the common unethical practices in various institutions for notation and avoidance by professionals.
Includes bibliographical references and index.
oif 23/10/14
Loan
Keywords: Professional ethics; Social reponsibility for business; Business ethics